PROCESS ANALYSIS RESULTS REPORTING CREDIT CARD COLLECTION ON CV. MIKA - Nanung Kristiawan; Jalinas, SKom, MM Jalinas, SKom, MM (Jurnal Sistem Informasi, 2003)
System is a network of procedures that are interconnected, gathered together toperform an activity or to accomplish a particular goal.The reporting system is an interconnected series of procedures to achieve a goal. Sothe reporting system is a system which contains reports from the billing credit cardcustomers conducted by a company billing services to banks that provide workthrough the existing means of information in order to be processed quickly andcorrectly in accordance with the request.